2022
DOI: 10.1039/d2cp02989h
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale simulation of proton diffusion in dislocation cores in BaZrO3

Abstract: Dislocations are important for their effects on the chemical, electrical, magnetic, and transport properties of oxide materials, especially for electrochemical devices such as solid fuel cells and resistive memories, but...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…For example, Yue et al. using quantum mechanical and molecular mechanical simulations found that in the regions of grain boundaries and dislocation cores in BaZrO 3 , the activation energy of proton transfer is increased because of the contribution of local lattice deformation . In addition, a more prosaic reason, that is, the presence of NiO, which was used as a sintering aid, may partially explain high activation energy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Yue et al. using quantum mechanical and molecular mechanical simulations found that in the regions of grain boundaries and dislocation cores in BaZrO 3 , the activation energy of proton transfer is increased because of the contribution of local lattice deformation . In addition, a more prosaic reason, that is, the presence of NiO, which was used as a sintering aid, may partially explain high activation energy.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been used to probe ion conduction in many systems, including ionic solids. In systems where moves can be cataloged, kinetic Monte Carlo (KMC) allows different time scale moves by choosing a move based on its probability and advancing the simulation clock based on the move’s rate constant. To overcome the challenges of both the distinct time and length scale important to ion conduction, a variety of multiscale methods have been developed and applied successfully to shed light on critical ion conduction technologies. , Many of these methods generate trajectories that can be probed to understand the system dynamics. Trajectories of ion conduction in solids may include many conducting ion diffusion steps near traps and a few escapes to fast conduction regions intermingled with smaller movements of other ions.…”
Section: Introductionmentioning
confidence: 99%
“… 6 9 To overcome the challenges of both the distinct time and length scale important to ion conduction, a variety of multiscale methods have been developed and applied successfully to shed light on critical ion conduction technologies. 10 , 11 Many of these methods generate trajectories that can be probed to understand the system dynamics. Trajectories of ion conduction in solids may include many conducting ion diffusion steps near traps and a few escapes to fast conduction regions intermingled with smaller movements of other ions.…”
Section: Introductionmentioning
confidence: 99%